APPROACH TO OPTIMIZATION HUSBANDRY OF KHARKIV REGION USING GIS MODELING - Добровольська, Наталія (Human Geography Journal, 2014)
The article is devoted to the problem of the ecological optimization of husbandry Kharkiv region in terms of rational use of natural conditions and economic gain. Holding geoinformation morphometric-surface hydrological modeling as a basis for further development of land management schemes at selected administrative districts of Kharkiv region is proved. Paying attention to important environmental problems of agriculture Kharkiv region – the intensification of erosion processes, which is due to irrational location of farmland and their considerable plowing.